(untitled) (Journal of the College of Education for Women, 2019)
At the beginning of 1935 theMinistry of (Yasin AL-Hashimi) was formed which was the result of the (Sulayikh)Conference .The new ministys policy was towards the authority of the one party and the exclusivity of power.The policy of (Yasin AL-Hashemi)has faced severe campaigns from the AL-Ekhaa and AL-Ahaly newspapers.The new ministry like its predecessor ministries . When it faces criticism from opposition newspapers .its shutting down newspapers and not accepting requests for them. Some opposition newspapers named Yassin AL-Hashemi (the dictator).Iraqi opposition newspapers have been neglected and deprived of press freedom although they were the main factor in educating the community and representing the public opinion of people . Lt appears that the Iraqi opposition newspapers during the period of the Iraqi monarchy ,despite the policy of neglect and looting of press freedoms were one of the most important reasons to topple successive ministries of the Iraqi state